Sikap Generasi “Z” terhadap bahasa Jawa: Studi kasus pada anak-anak usia Sekolah Dasar di kota Semarang - Ilham Setyawan (Program Studi Ilmu Komunikasi FBIK Unissula, 2019)
Language in everyday life has a very important role in communicating. At present there has been a decline in interest in the use of Javanese as a communication tool for the “Z” generation, namely the generation born in 1994-2012. The aim of this study is to find out the intensity of the use of regional languages, especially the Javanese language by the “Z” generation, what is the impact of the loss of regional languages, especially the Javanese language for the identity of the region and how the generation of “Z” language attitudes to local languages are specifically Javanese . From this study it was found that, “Z” generation has the ability that is very lacking in communicating using Javanese. The things that affect their mastery in language include their buccal background originating from the Javanese, the lack of use of the Javanese language as a daily communication tool and the lack of innovation in Javanese language learning methods. From this, innovation in learning is needed as well as increasing the intensity of the use of Javanese as a daily communication tool. Parents and teachers in the school have a role in mastering the Javanese language in communicating.